SOSIALISASI OLAHRAGA PANAHAN KEPADA MASYARAKAT RT 006 RW 001 DI KAMPUNG TANJAKAN DESA TANJAKAN DI ERA PANDEMI - Muhammad Rifky Anugrah; Apta Mylsidayu; Mia Kusumawati (An-Nizam, 2022)
The spread of cases of the Covid-19 virus, both in the world and in Indonesia in particular. Efforts that must be continued are by consuming nutritious food, complying with health protocols, vaccinating and maintaining body immunity through exercise. One of them is archery. Archery can help strengthen the immune system or body immunity. To prevent infection with the Covid-19 virus. In addition, archery can help get out of boredom due to the pandemic which has not yet ended. The problem is that in this activity, people do not know and lack understanding about the sport of archery. Therefore, this socialization activity aims to increase knowledge and understanding of the sport of archery. This socialization will be held from March 1, 2022 to March 11, 2022 at RT 006 RW 001 in Tanjakan Village, Tanjakan Village. The target of this outreach activity is to the Community of RT 006 RW 001 in Tanjakan Village. The method of implementation is through direct introduction to archery equipment, conducting webinars that discuss the brief history of archery, various types of archery bows, equipment in archery, basic archery techniques, and direct practice of basic archery techniques by modifying archery bows. using a palaron in which bamboo has been inserted in the palaron so that the results of maximum whipping and direct practice still follow the health protocols in the era of the Covid-19 pandemic. As a result of this socialization, the community in RT 006 RW 001 in Tanjakan Village is more familiar with the history of archery, basic archery techniques, equipment used when archery, and the community is very enthusiastic and enthusiastic in participating in this outreach activity.